The information content from lending relationships across the supply chain - Martins, Theo Cotrim; Schiozer, Rafael; Linardi, Fernando de Menezes (Journal of Financial Intermediation, 2023)
Using unique administrative data on firm-to-firm payments and bank-to-firm lending, we investigate how lending to a firm is affected by same-bank lending to the firm's customers and suppliers. We show that the supply of loans to a firm increases when the firm's customers have loans from the same bank. We also find that negative information about a firm's top customer causes banks to tighten the loan supply to the firm, and particularly more so when the firm's sales are concentrated on this customer. These results suggest that lending to firms connected through the supply chain conveys valuable information to banks.